Serum leptin and cholesterol levels in patients with bipolar disorder - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B; Bayik, Y (Karger, 2002)
Low cholesterol levels have been reported in patients with manic episodes. Leptin seems to be strongly associated with lipid metabolism. In the present study, therefore, serum total cholesterol and leptin levels were compared in 16 patients with manic episodes, 16 with bipolar I disorder in full remission and 16 healthy controls. The serum total cholesterol and leptin levels were measured and Young Mania Rating (YMRS) and Hamilton Depression Rating Scales (HAM-D) were administered for each subject. Both the patients with manic episodes and the patients with bipolar I disorder in full remission had markedly low serum cholesterol and leptin levels compared with controls, though the difference was more obvious in patients with manic episodes. In addition, there were negative correlations between YMRS scores and serum cholesterol or leptin levels in the patients with manic episodes. Our results suggest that the patients with manic episodes and those with bipolar I disorder in full remission seem to be associated with decreased serum cholesterol and leptin levels. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: leptin; cholesterol; manic episode; bipolar disorder